2010
DOI: 10.1007/s00296-010-1381-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psychological status and disease activity and quality of life in ankylosing spondylitis

Abstract: Our aim in this study was to compare the depression and anxiety risk in patients with AS and healthy controls and also to determine the relationship between disease activity, quality of life and psychological well-being. Two hundred and forty-three patients with ankylosing spondylitis (AS) and 118 age-, sex- and education-matched healthy controls were enroled into the study. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and Functional Index, and Metrology Index, Health Assessment Questionnaire f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
96
7
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 32 publications
14
96
7
11
Order By: Relevance
“…Previous studies investigating the relationship between depression and disease activity in AS have also revealed similar results. 22,23 As a result of our findings, we suggest that assessment of disease activity in patients with AS particularly by a patient-reported outcome measure such as BASDAI must include assessment of depression, which may potentially affect these scores. We recommend that treatment decisions and alterations should be made after treatment of accompanying depression if noted.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies investigating the relationship between depression and disease activity in AS have also revealed similar results. 22,23 As a result of our findings, we suggest that assessment of disease activity in patients with AS particularly by a patient-reported outcome measure such as BASDAI must include assessment of depression, which may potentially affect these scores. We recommend that treatment decisions and alterations should be made after treatment of accompanying depression if noted.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have consistently shown significantly higher anxiety ve depression scores in AS patients compared to control groups. In one study using the HADS tool, Baysal et al (8) reported significantly higher anxiety scores among AS patients but no significantly difference in depression scores versus control group. Studies have looked at other parameters such as quality of life (6), disability (5), sexual dysfunction (25), and alexithymia (26) in addition to anxiety and depression and found considerable impairment in these areas.…”
Section: Discussionmentioning
confidence: 97%
“…Anxiety and depression are among the most commonly investigated psychiatric conditions among AS patients (5)(6)(7)(8)(9). Previous studies have consistently shown significantly higher anxiety ve depression scores in AS patients compared to control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS is an inflammatory condition that causes significant pain, functional disability and a diminished quality of life [1][2][3]. Combining exercise therapy with medication is standard for patients with AS, as suggested by the Spondylitis Association of America [4].…”
Section: Discussionmentioning
confidence: 99%